THE ANALYSIS OF STUDENTS ERROR IN USING RELATIVE CLAUSE - Stevyara Rismawathi Kusdianty (Universitas Kuningan, 2016)
This study is aimed at investigating error types of Relative Clause and focuses on error of selection items of relative pronoun. Limitation of the study was on the students error in using relative pronoun (who, whom, which, and whose) in Report Text and the causes of the students error. This study used descriptive qualitative method. There were two techniques of collecting the data; observation which aimed at giving relative pronoun test in Report Text and interview which aimed at gathering information about the causes of the students made error. 20 students from class XI IPA 1 and XI IPA 2 of SMAN 1 Garawangi were chosen by the researcher as the sample of this study. The theory by Corder (1982), Azar (1999) and Brown (2000) were used as a basic theory to analyze the collected data. Finally, the results of the analysis showed that the students made errors in relative pronoun who with number 45 errors or 33.6%. The error in using relative pronoun whom were 32 errors or 23.9%. The error in using relative pronoun which were 29 errors or 21.6%. The error in using relative pronoun whose with number 28 errors or 20.9%. The errors caused by the influences of intralingual transfer or most of the students didnt understand about the material, and interlingual transfer or the influences from their mother tongue in pronouncing and writing relative pronoun.